A Novel Combination of Calprotectin and CXCL12 for Predicting Malignancy in Patients with Exudative Pleural Effusion. Issue 47 (November 2015) - Luo, Jian; Wang, Maoyun; Li, Chuntao; Liang, Binmiao; Liu, Dan; Shi, Chaoli; Jiang, Faming; Wang, Ting; Li, Peijun; Liang, Zongan
Abstract : Abstract: Pleural effusion (PE) remains a significant challenge and public health problem, which needs novel noninvasive biomarkers for the precise diagnosis. The aim of this study was to further determine the clinical efficacy and diagnostic accuracy of a novel combination of calprotectin and CXCL12 for predicting malignancy in patients with exudative PE. Calprotectin and CXCL12 concentrations were measured in 95 individuals of exudative PE, with 39 malignant PE (MPE) and 56 benign PE (BPE). The accuracy of calprotectin and CXCL12 levels for discriminating MPE from BPE or tuberculous PE were evaluated using receiver-operating characteristic (ROC) curves. Univariate and multivariate logistic regression analyses were performed to test the association between calprotectin and CXCL12 levels and MPE. Calprotectin and CXCL12 levels of patients with MPE were significantly lower than that of BPE and tuberculous PE ( P  < 0.05). The area under the curve (AUC) of calprotectin and CXCL12 was 0.683 and 0.641 in MPE and BPE, and a combination of calprotectin ⩽500.19 ng/mL and CXCL12 ⩽6.11 ng/mL rendered a sensitivity and specificity of 48.72% and 78.57%, respectively. While in MPE and tuberculous PE, the AUC of calprotectin and CXCL12 was 0.696 and 0.690, and a combination of calprotectin ⩽421.73 ng/mL and CXCL12 ⩽3.71 ng/mL presented a sensitivity and specificity of 25.64% and 95.45%, respectively. Multivariate logistic regression demonstrated that both calprotectin and CXCL12 were independent predictors of MPE. Calprotectin and CXCL12 in pleural fluid are informative diagnostic biomarkers for predicting patients with MPE.